2001
DOI: 10.1007/pl00000854
|View full text |Cite
|
Sign up to set email alerts
|

HuR and mRNA stability

Abstract: An important mechanism of posttranscriptional gene regulation in mammalian cells is the rapid degradation of messenger RNAs (mRNAs) signaled by AU-rich elements (AREs) in their 3' untranslated regions. HuR, a ubiquitously expressed member of the Hu family of RNA-binding proteins related to Drosophila ELAV, selectively binds AREs and stabilizes ARE-containing mRNAs when overexpressed in cultured cells. This review discusses mRNA decay as a general form of gene regulation, decay signaled by AREs, and the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
978
1
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 971 publications
(1,012 citation statements)
references
References 121 publications
20
978
1
7
Order By: Relevance
“…VEGF mRNA is extremely labile in normoxic conditions, with a half-life of less than 1 hour, as compared with the average halflife of 10 to 12 hours for eukaryotic mRNA. During hypoxia, the half-life of VEGF mRNA increases by two to three-fold (Levy et al, 1996) due to a stabilizing effect of HuR, a 36 kDa RNA-binding protein, which binds with high affinity to AREs in the 3′-UTR of VEGF mRNA, protecting it from degradation by endonucleases (Brennan and Steitz, 2001;Robinow et al, 1988).…”
Section: Regulation Of Vegf Expressionmentioning
confidence: 99%
“…VEGF mRNA is extremely labile in normoxic conditions, with a half-life of less than 1 hour, as compared with the average halflife of 10 to 12 hours for eukaryotic mRNA. During hypoxia, the half-life of VEGF mRNA increases by two to three-fold (Levy et al, 1996) due to a stabilizing effect of HuR, a 36 kDa RNA-binding protein, which binds with high affinity to AREs in the 3′-UTR of VEGF mRNA, protecting it from degradation by endonucleases (Brennan and Steitz, 2001;Robinow et al, 1988).…”
Section: Regulation Of Vegf Expressionmentioning
confidence: 99%
“…In mammals and in Xenopus, the Hu family consists of three members that are developmentally regulated and tissue-specific-Hel-N1 (also called HuB), HuC, and HuD-and one (HuR) that is ubiquitously expressed in all cell types (Szabo et al, 1991;King et al, 1994;Good, 1995;Ma et al, 1996;Antic and Keene, 1997). HuR is the best-characterized ELAV protein Brennan and Steitz, 2001;Wilusz et al, 2001). It has a high binding affinity for several AREs Good, 1997;Levy et al, 1998;Maurer et al, 1999;Sakai et al, 1999;Sokolowski et al, 1999), and although predominantly nuclear, it shuttles between the nucleus and the cytoplasm, affecting mRNA stability and translation (Fan and Steitz, 1998).…”
Section: Hurmentioning
confidence: 99%
“…The subsequent analysis of the CD83 transcript revealed that this mRNA contains in its coding region, a highly structured cis-active RNA sequence, termed the post-transcriptional regulatory element (PRE), and that this RNA element is directly recognized by the cellular RNA-binding shuttle protein HuR [32]. Interestingly, PRE:HuR interaction does not affect, as it was shown with other HuR targets such as early response gene mRNA [33], the stability of this transcript. Instead, this interaction induces the CRM1-dependent cytoplasmic accumulation of CD83 mRNA [32].…”
mentioning
confidence: 94%